The helminth fauna of the terrestrial vertebrates from S. Miguel Island (Azores) : an annotated checklist of known species - Afonso-Roque, Maria Manuela (2013)
Submitted by RUA REPOSITORIO (repositorio@uac.pt) on 2013-07-02T14:58:31Z No. of bitstreams: 1 LMSpp99-104AFONSO-ROQUE_N13A.pdf: 1050035 bytes, checksum: 5513bff2fcfb74a9fe72be4278890a71 (MD5)